Effect of ZrO2 on the structure, hardness and humidity sensing properties of TiO2-ZrO2 / Siti Nurul Shahmimie Sulaiman - Sulaiman, Siti Nurul Shahmimie (Faculty of Applied Sciences, 2017)
The influence of ZrO2 on the structural, hardness and humidity sensing properties of the TiO2 ceramics were investigated. The samples were prepared by the conventional ceramic method. The samples were characterized on their structure, hardness and humidity sensitivity. Analysis on the hardness properties has been carried out using Vickers hardness and bulk density method. It shows that hardness of samples do not affected by the bulk density. Field Emission Scanning Electron Microscopy (FESEM), X-ray Diffractometer (XRD) and impedance spectroscopy method were used for characterization the microstructure and sensing properties of samples. The average grain size shows significant difference between each samples. The XRD analysis support the characteristic of the average grain size of the samples. The ratio of impedance indicate the sensitivity of samples. Sample with Zr02 addition of 20 wt% have the highest ratio of impedance and sensitivity for ceramic composite rather than other samples at two different %RH which is 56 %RH and 27 %RH.